An Innovative Adaptive Threshold-Based BESS Controller Utilizing Deep Learning Forecast for Peak Demand Reductions - MD Mahmudul Hasan; Yun Seng Lim; Lee Cheun Hau; Xie Cherng Miow; Jianhui Wong; Dylon Hao Cheng Lam; Nor Shahida Hasan; Hamzah B. Adlan (IEEE Access)
Battery-based energy storage systems (BESS) can be installed and controlled by a control strategy to reduce daily peak demands. Majority of the existing controllers for BESS is developed and studied on a simulation platform. Hence, an innovative adaptive threshold-based controller is developed and implemented on a real 200 kWh BESS installed on a university campus in Malaysia to reduce daily peak demands. This controller is developed on the free, open-source Node-RED platform using a deep learning-based one-dimensional convolution neural network (1D-CNN) to forecast the load profile for one day ahead. The controller uses the forecasted load profile to define a threshold or specific power demand level above which the BESS will start discharging power to meet the demand. The threshold is actively adjusted according to the actual and forecasted power demand of the customer as well as preceding peak of the grid power. The performance of the controller is initially assessed through six months of comprehensive simulations, where its daily peak reduction factor ( $K_{pdr}$ ) and monthly peak reduction failure rate ( $η _{failure}$ ) are compared with that of two fixed-threshold controllers, namely forecasted threshold and historical threshold-based controllers, and another two advanced controllers, namely active and fuzzy controllers. The adaptive threshold-based controller achieves an average $K_{pdr}$ of 41.62% and $η _{failure}$ of just 16.55%, which are better than that of other four controllers. The controller is implemented to BESS in a university building to evaluate its practical performance over 21 days under a real operating condition. The controller achieves an average $K_{pdr}$ of 49.45% with a $η _{failure}$ of just 4.76%, which are better than the simulation results.